Effect of two recovery strategies on performance recovery: Cold-water immersion vs whole-body cryotherapy - Abaidia, A.; Lamblin, J.; Delecroix, B.; Leduc, C.; McCall, A.; Nedelec, M.; Dawson, B.; Baquet, G.; Dupont, G. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Cold-water immersion and whole-body cryotherapy are two commonly used strategies to accelerate recovery following muscle-damaging exercise. Some studies have shown a positive effect of both strategies on accelerating the recovery kinetics (Ingram et al., 2009; Ferreira-Junior et al., 2015). However, to our knowledge, no study has yet compared these two strategies in direct competition with each other. The purpose of this study was therefore to investigate which recovery strategy; cold-water immersion versus whole-body cryotherapy was more effective at enhancing the recovery kinetics following a muscle-damaging exercise. Methods: In a randomized cross-over design, ten subjects performed a muscle-damaging exercise protocol: 5 sets of 15 single leg eccentric contractions for the hamstring muscle. Immediately following the exercise, subjects were either, immersed in cold-water (10 minutes at 10°C) or exposed to whole-body cryotherapy (3 minutes at -110°C). The recovery kinetics were assessed immediately, 24h, 48h and 72h after the muscledamaging exercise. Specifically, the recovery protocol consisted of measuring; creatine kinase, hamstring maximal force, countermovement jump height, perceived muscle soreness and perceived recovery. Results: A very likely (99% and 97%) moderate effect was found in favour of cold-water immersion for one-leg (Effect Size=-0.63; 90% CI=-1.38 to 0.13) and two-leg countermovement jump (ES=-0.68; 90%CI=-1.43 to 0.08) 72h after exercise respectively. The perceived muscle soreness was moderately lower 48h after exercise in the coldwater immersion condition (ES=0.68; 90% CI=-0.07 to 1.44). Perceived recovery was moderately improved 24h after the exercise in the cold-water immersion group (ES=0.62; 90% CI=-0.13 to 1.38). Trivial and small effects of condition were found for the other outcomes. Discussion: According to the findings in the present study, cold-water immersion was more efficient to accelerate recovery kinetics compared to whole-body cryotherapy. Specifically, recovery was enhanced for one and two-leg countermovement jump 72h post-exercise. Cold-water immersion also showed a greater ability to reduce perceptions of muscle-soreness and improve the level of perceived recovery. In regards to muscle strength indices, there was no difference in recovery between both strategies.